Asynchronous accumulation of sugar and phenolics in grapevines following post-veraison leaf removal - Mewael Kiros Assefa; Glen L. Creasy; Rainer W. Hofmann; Amber K. Parker (OENO One)
Climate change necessitates the re-evaluation of viticultural practices to manage increasing grape sugar concentrations and meet consumer demand for lower-alcohol wines. This study aimed to evaluate whether modifying the leaf area to fruit weight (LA:FW) ratio through shoot trimming could reduce sugar accumulation while maintaining phenolic quality in Pinot noir grapes. We examined both the timing and severity of canopy reduction, implementing shoot trimming treatments (half canopy, H, in 2015–2016 and 2016–2017, and quarter canopy, Q, in 2016–2017) at three stages: pre-veraison (V–, E-L 34), veraison (V, E-L 35), and post-veraison (V+, E-L 36) across three vineyard locations. In each trimmed treatment (H or Q), lateral shoots were removed concurrently with shoot trimming to maintain consistent leaf area. Our results show that reducing the LA:FW ratio through trimming delayed and reduced grape sugar accumulation. Phenolic responses, however, varied by timing: early trimming (V–, V) decreased anthocyanin concentration at harvest of up to 37 % in QV- vines compared to controls, primarily due to reduced accumulation rates. In contrast, late trimming (QV+, HV+) maintained the concentration of anthocyanins at harvest and at target soluble solids and preserved anthocyanin-to-sugar ratios similar to the control. Total phenols, seed and skin tannins were unaffected by trimming, particularly in QV+ and HV+ treatments. Therefore, while these treatments decreased soluble solids, these phenolic components remained unchanged. Our results demonstrated that post-veraison (V+) shoot trimming could be a promising strategy to produce darker-colored berries at lower sugar concentrations. Therefore, trimming post-veraison but early in the maturity phase (~15 °Brix) to half-canopy level (HV+), represents a more sustainable approach for achieving dark-colored grapes while maintaining unaltered phenolic profiles at lower sugar concentrations.